Application of RME to Improve Numeracy and Reduce Math Anxiety using Liveworksheets and Geogebra - Aziz, Aliyah; Septian, Ari; D, Siti Rohani; R, Rizka Awaliyah; R, Marchantia Tatiana; Nurhalim, Rizpan (PRISMA, 2025)
This study aims to evaluate improvements in numeracy skills and reductions in students' mathematical anxiety by implementing Realistic Mathematics Education (RME) in the Kurikulum Merdeka using Liveworksheets and GeoGebra media. The research method used is the quasi-experiment. The design of this study uses nonequivalent comparison group design. The population in this study were students of class X SMAN 1 Cibeber in the 2024/2025 academic year. From this population, two classes were taken as samples, namely the class that would become experimental group 1 and experimental group 2 which were selected using the purposive sampling technique. Experimental group 1 received intervention with the Realistic Mathematics Education (RME) model based on Liveworksheets and GeoGebra media, and experimental group 2 (control class) received intervention with conventional learning methods. The instruments used were test and non-test instruments (in the form of questionnaires). The material used was about exponent material. Data analysis was carried out on the average gain index between the two sample classes utilizing the similarity of two averages. The results of the research show that in the research process, there was an increase in students' numeracy skills and overcoming mathematical anxiety, in this case, those who used intervention with the Realistic Mathematics Education (RME) model based on Liveworksheets and GeoGebra media were better than learning using conventional learning methods. The increase in numeracy ability in the experimental class obtained an n-Gain score of 0.24 while in the control class it obtained an n-Gain score of 0.17. The final level of mathematical anxiety in the experimental class obtained an average score of 64 while the control class obtained an average score of 65.189. However, the experimental class experienced a significant increase of 36.79% in changes in students' mathematical anxiety.